From Financieristic to Real Macroeconomics : Seeking Development Convergence in Emerging Economies - Ffrench-Davis, Ricardo (World Bank, Washington, DC, 2017)
Macroeconomic "fundamentals" are a most relevant variable for economic development. However, there is wide misunderstanding about which are the "sound macroeconomic fundamentals," contributing to sustained economic growth. The approach in fashion in the mainstream world and international finance institutions (IFIs) emphasizes macroeconomic balances of two pillars: low inflation and fiscal balances. The author calls it financieristic macroeconomic balances. Additionally, a frequent assertion in the conventional literature is that an open capital account contributes to impose macroeconomic discipline in emerging economies (EEs). There is strong evidence that financieristic balances have not provided a macroeconomic environment contributing to sustained growth. A third pillar must be added, linked to the productive side of the economy. The behavior of aggregate demand, at levels consistent with potential gross domestic product (GDP), is a crucial part of a third pillar for real macroeconomic balances, which has frequently failed in neoliberal experiences. Similarly crucial parts are well-aligned macro-prices, like interest and exchange rates. Frequently, these prices and aggregate demand have behaved as outliers, as reflected in economies working either well below potential GDP (the most frequent result), or overheated, with a booming aggregate demand and a large external deficit. This paper analyses alternative macroeconomic environments faced by firms and workers in the productive side of the economy (the producers of GDP), and the interrelationship between financial and real variables. The author analyzes alternative structural countercyclical fiscal policies, intermediate exchange rate policies, and capital account approaches.